Impediments to the prompt carrying out of some of the principles conceded by Parliament on the Irish land question - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1879)
In this paper I do not propose to deal with any principles as applied to the Irish land question, except those which have already been conceded by Parliament. With respect to one branch of the land question?the encouragement and facilities for the creation of peasant proprietors?a very elaborate inquiry has been made by Mr. Shaw Lefevre's committee, to ascertain the impediments to the successful working of what are called the Bright clauses. I propose to state the results of a scientific investigation, on principles of economic science and jurisprudence, of the impediments to the working of some of the other clauses of the Land Act.
Read before the Society, August 1878
Keywords: Irish land question; Land reform; Land ownership in Ireland; Bright clauses; 314.15